DECISION SUPPORT SYSTEM FOR SELECTION OF HOME OWNERSHIP LOANS (KPR) USING THE SMART METHOD - Dewi Lestari, Candra; Gito Resmi, Mochzen; Raymond Ramadhan, Yudhi (RISTEC : Research in Information Systems and Technology, 2022)
The bank is a financial institution that has many activities, oneof which is to serve housing loan (KPR) activities. As the human population increases, primary needs such as housing also increase. The existence of a Developer who will provide Home Ownership Loans is also needed for prospective buyers. With various offers, potential home buyers are difficult to make a decision. Therefore the authors through the Decision Support System (SPK) and thedesign of the Home Ownership Loan system providea solution for prospective buyers in choosing the best mortgage with a Decision Support System using the SMART method. The SMART method is a multi-criteria decision-making technique based on the theory that each alternative consists of a number of criteria that have values and each criterion has a weight that describes how important it is compared to other criteria.